Recognition Memory After Febrile Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at the Institute of Child Health, London; Epilepsy Center, University of Edinburgh; and Dartmouth Medical School, New Hampshire, US studied memory abilities in 26 children (mean age 23 months, SD 12.6 months) after prolonged febrile seizures (median, 37.5 days), and compared to 37 normal controls.